Desenvolvimento de um Piranômetro portátil com sensores termorresistivos - Sesso, Maria da Graça Vasconcelos (1989)
An alternative approach to develop, design and construct a portable pyranometer with non-conventional thermoresistive sensors is presented and analysed. Theoretical relations based on the functioning principie of its sensors, using a Wheatstone bridge arrangement with a battery power supply are compared to experimental responses, both static and dynamic, obtained by the Computer processing of a data acquisition system. Characteristics of the instrument such as the steady-state sensitivity of 1,43 x 10~6 V/W m-2, resolution of 7,0 W/m2, time constant of 17,75 s, linearity of + 1%, deviation of ± 5% related to cosine effect, of ± 3% related to the tilting effect and of ± 1 % related to environmental temperature variation effects, were used for its classification as 2nd class instrument /according to the World Radiation Center criteria. Its simplicity, compared to other measuring systems that use a similar process of conversion, as well as its viability, prove the contribution of this research.